BASIC DIRECTIONS OF DEVELOPMENT OF THE GLOBAL EDUCATION SYSTEM - Гулиев, Н. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The article analyzes the perspectives of education development that are at the epicenter of processes that are undergoing globalization. The knowledge required for an individual to understand the processes of globalization and to actively participate in these processes is demonstrated. Dynamics and internationalization of education, the presence of various close links between different components of the international education system, and the increase in the concentration of education systems are all about the features inherent in the modern world. At the same time it is justified by the need to formulate a new educational philosophy based on the universal and national values of society and address the issues of revival of the spiritual life of the society. It is indicated that today education is the key to the labor market. A good education is the basis for a successful responsible life and social participation, the best protection against the risk of unemployment. It is estimated that people without an education are almost three times more likely to be unemployed than people with an education diploma. In connection with the foregoing, the aim of the article is to justify the provision that many can take advantage of the opportunities arising from the processes of globalization. The importance of the methodology and tools used in such sciences as cultural anthropology and ethnology is proved. The information obtained by these sciences provides a wealth of factual and empirical material for understanding not only the past and present, but also future education